INVESTIGATION ON THE MECHANISM OF ACTION OF THE LEAVES OF TRIANTHEMA PORTULACASTRUM ON HUMAN PATHOGENS - D, Kavitha; S, Vidhya; PR, Padma (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Many of the plants are used for medicinal purposes in human health needs. Trianthema portulacastrum has got many medicinal values and also a dietary plant, being used in Ayurveda. It exhibits nephroprotective, diuretic, anti-cancerous, antihelmintic, antipyretic, analgesic properties, anti-inflammatory activity, and also antibacterial activity. The objective of this study is to determine the mechanism of action of the leaves of T. portulacastrum on human pathogens. Methods: The mechanism has been analyzed by membrane permeability, time-kill kinetics, hemolytic activity, DNA binding ability, post antibiotic effect, and bacterial membrane damage by scanning electron microscopy. Results: This study reveal that the flavonoid and methanol fractions of T. portulacastrum have potent antibacterial activity against Staphylococcus aureus and Klebsiella pneumoniae. The leaves of T. portulacastrum has been proved as a safer drug indicating its noncytotoxic property and found to kill the bacterial cells by permeating the membrane and damage the DNA of the bacterial cells. Conclusion: This study proved the mode of antibacterial action of T. portulacastrum on S. aureus and K. pneumoniae indicating its antibacterial efficacy on human pathogens. Keywords: Staphylococcus aureus, Postantibiotic, Klebsiella pneumoniae, Trianthema portulacastrum.